Fabrication and Characterization of Tedizolid Phosphate Nanocrystals for Topical Ocular Application: Improved Solubilization and In Vitro Drug Release - Mohd Abul Kalam; Muzaffar Iqbal; Abdullah Alshememry; Musaed Alkholief; Aws Alshamsan (MDPI AG, 2022)
Positively charged NCs of TZP (0.1%, w/v) for ocular use were prepared by the antisolvent precipitation method. TZP is a novel 5-Hydroxymethyl-Oxazolidinone class of antibiotic and is effective against many drug-resistant bacterial infections. Even the phosphate salt of this drug is poorly soluble, therefore the NCs were prepared for its better solubility and ocular availability. P188 was found better stabilizer than PVA for TZP-NCs. Characterization of the NCs including the particle-size, PDI, and ZP by Zeta-sizer, while morphology by SEM indicated that the preparation technique was successful to get the optimal sized (151.6 nm) TZP-NCs with good crystalline morphology. Mannitol (1%, w/v) prevented the crystal growth and provided good stabilization to NC1 during freeze-drying. FTIR spectroscopy confirmed the nano-crystallization did not alter the basic molecular structure of TZP. DSC and XRD studies indicated the reduced crystallinity of TZP-NC1, which potentiated its solubility. An increased solubility of TZP-NC1 (25.9 µgmL−1) as compared to pure TZP (18.4 µgmL−1) in STF with SLS. Addition of stearylamine (0.2%, w/v) and BKC (0.01%, w/v) have provided cationic (+29.4 mV) TZP-NCs. Redispersion of freeze-dried NCs in dextrose (5%, w/v) resulted in a clear transparent aqueous suspension of NC1 with osmolarity (298 mOsm·L−1) and viscosity (21.1 cps at 35 °C). Mannitol (cryoprotectant) during freeze-drying could also provide isotonicity to the nano-suspension at redispersion in dextrose solution. In vitro release in STF with SLS has shown relatively higher (78.8%) release of TZP from NC1 as compared to the conventional TZP-AqS (43.4%) at 12 h. TZP-NC1 was physically and chemically stable at three temperatures for 180 days. The above findings suggested that TZP-NC1 would be a promising alternative for ocular delivery of TZP with relatively improved performance.